Amino acid sequence of Japanese quail (Coturnix japonica) and northern bobwhite (Colinus virginianus) myoglobin. (15th August 2015) - Goodson, John; Beckstead, Robert B.; Payne, Jason; Singh, Rakesh K.; Mohan, Anand
Highlights: Amino sequence of Japanese quail and northern bobwhite myoglobin was determined. Both species' myoglobin structures consist of 153 amino acids. Japanese quail myoglobin showed 98% sequence homology with chicken. Japanese and northern bobwhite quail myoglobin shared 97% of sequence homology. Abstract: Myoglobin has an important physiological role in vertebrates, and as the primary sarcoplasmic pigment in meat, influences quality perception and consumer acceptability. In this study, the amino acid sequences of Japanese quail and northern bobwhite myoglobin were deduced by cDNA cloning of the coding sequence from mRNA. Japanese quail myoglobin was isolated from quail cardiac muscles, purified using ammonium sulphate precipitation and gel-filtration, and subjected to multiple enzymatic digestions. Mass spectrometry corroborated the deduced protein amino acid sequence at the protein level. Sequence analysis revealed both species' myoglobin structures consist of 153 amino acids, differing at only three positions. When compared with chicken myoglobin, Japanese quail showed 98% sequence identity, and northern bobwhite 97% sequence identity. The myoglobin in both quail species contained eight histidine residues instead of the nine present in chicken and turkey.